COMPARATIVE ANALYSIS OF COST RECOVERY AND GROSS SPLIT MECHANISMS IN OIL AND GAS PROJECTS IN INDONESIA - Hana Dirda Hutapea; Aisyah Naila; Cassie Gabriellia; Nita Harintan; Putri Tantya5 Putri Tantya5 (Problematika Hukum, 2023)
This journal presents a comparative analysis of the cost recovery and gross split mechanisms in oil and gas projects in Indonesia. The cost recovery and gross split procedures utilized in Indonesian oil and gas projects are compared in this research. The objective is to evaluate the benefits and drawbacks of each mechanism and pinpoint the variables that affect the mechanism that businesses select. While gross sharing mandates that corporations share earnings with the government from the outset of production, cost recovery permits companies to recover their production and exploration costs before sharing revenues with the government. The journal presents that while gross sharing increases government revenue and lowers the likelihood of cost overruns, cost recovery provides businesses with greater certainty but also exposes them to higher risks. The project's size, the level of government involvement, and the political and regulatory landscape all influence the method chosen. To help stakeholders in the business and policymakers choose the best procedures for their projects, the studies also offer insightful information.Keywords: Cost Recovery ; Gross Split ; Corporations ;